An ERF2-like transcription factor regulates production of the defense sesquiterpene capsidiol upon Alternaria alternata infection. (10th July 2019) - Song, Na; Ma, Lan; Wang, Weiguang; Sun, Huanhuan; Wang, Lei; Baldwin, Ian T; Wu, Jinsong
Abstract : Capsidiol, a phytoalexin accumulated in Nicotiana attenuata in response to Alternaria alternata attack, plays an important role in pathogen resistance, and its biosynthesis is transcriptionally regulated by an ERF2-like transcription factor. Abstract: Capsidiol is a sesquiterpenoid phytoalexin produced in Nicotiana and Capsicum species in response to pathogen attack. Whether capsidiol plays a defensive role and how its biosynthesis is regulated in the wild tobacco Nicotiana attenuata when the plant is attacked by Alternaria alternata (tobacco pathotype), a notorious necrotrophic fungus causing brown spot disease, are unknown. Transcriptome analysis indicated that a metabolic switch to sesquiterpene biosynthesis occurred in young leaves of N. attenuata after A. alternata inoculation: many genes leading to sesquiterpene production were strongly up-regulated, including the capsidiol biosynthetic genes 5- epi - aristolochene synthase ( EAS ) and 5- epi - aristolochene hydroxylase ( EAH ). Consistently, the level of capsidiol was increased dramatically in young leaves after fungal inoculation, from not detectable in mock control to 50.68±3.10 µg g −1 fresh leaf at 3 d post-inoculation. Capsidiol-reduced or capsidiol-depleted plants, which were generated by silencing EAH s or EAS s by virus-induced gene silencing, were more susceptible to the fungus. In addition, this sesquiterpene when purified from infected plants exhibited strong anti-fungal activities against A. alternata in vitro . Furthermore, an ERF2-like transcription factor was found to positively regulate capsidiol production and plant resistance through the direct transactivation of a capsidiol biosynthetic gene, EAS12 . Taken together, our results demonstrate that capsidiol, a phytoalexin highly accumulated in N. attenuata plants in response to A. alternata infection, plays an important role in pathogen resistance independent of jasmonate and ethylene signaling pathways, and its biosynthesis is transcriptionally regulated by an ERF2-like transcription factor.